Audit in ultrasound: An introduction and overview. Issue 3 (24th March 2022) - Moore, Stephen; Reeve, Ruth
Abstract: This article highlights the importance of clinical audits within ultrasound and provides an overview of how audits can guide high‐quality clinical care and lead advanced practice within Ultrasound. We outline the who, what when and where of audit and how it can be used in contemporary medicine. Utilising the frameworks within the United Kingdom from the British Medical Ultrasound Society and others as well as drawing from personal experience the authors demonstrate practical examples of audits that have improved the quality of care within the United Kingdom and lead the way for Advanced Practitioner roles where individuals undertake interventional procedures such as Fine Needle Aspirations. The aim of this articles is to demonstrate how Sonographers can take their audits forward and implement the clinical environment. Abstract : To access CPD test for this article click here: https://www.sonographers.org/cpds/Audit_in_ultrasound_an_introduction